The rare genus Leptospathius Szépligeti (Hymenoptera, Braconidae, Doryctinae) from China, with description of a new species - Tang, Pu; Wu, Qiong; Belokobylskij, Sergey; Chen, Xuexin (Zootaxa, 2012)
The Chinese Leptospathius Szépligeti, 1902, from the Parasitic Hymenoptera Collection of Zhejiang Universitywas studied and two species were recognized. A new species of this genus, L. hunanensis sp. nov., is described and illustrated. A key to the Oriental species of this genus is provided.